The Importance of Serological Procalcitonin Levels After Autologous Microsurgical Transplantation. Issue 3 (May 2019) - Safi, Ali-Farid; Schröder, Kai; Kauke, Martin; Safi, Sema; Zöller, Joachim E.; Zinser, Max
Abstract : Introduction: Published data on procalcitonin (PCT) levels after microsurgical interventions are very scarce, although infection within these patients is not only associated with severe morbidity but also significantly higher mortality rates. Material and Methods: Retrospective study on 20 patients, who were operated on by a single experienced plastic and reconstructive surgeon within one year (June 2017–June 2018). The authors included all patients, who received microvascular transplants for reconstruction of soft tissue defects. Furthermore, age above 18 years and appropriate documentation allowing sufficient data collection were defined as inclusion criteria. The authors excluded all patients with perioperative systemic inflammation and transplant loss, as our aim was to solely determine and evaluate potential alterations of serological PCT levels after microsurgical interventions. Results: The PCT cutoff level to differentiate physiological and pathological levels was defined as 0.1 μg/L. There was no detectable increase in procalcitonin in all of our 20 patients, for whom the authors performed microvascular transplantation to reconstruct soft tissue defects. Conclusion: Serological PCT levels remain stable after the considered surgical interventions and therefore PCT levels might be utilized to identify systemic inflammation, thus helping to reduce severe complications by early individualized antiinfective treatment strategies.